Divergent trends in structural landscape connectivity from historic and potential future grassland conversion in Alberta, Canada - Hossam E. Abdel Moniem; Majid Iravani; Tim McAllister; Kim Ominski; Helene H. Wagner (PLoS ONE, 2025)
Grasslands across the Canadian prairies are crucial for maintaining biodiversity and ensuring landscape connectivity. In Alberta, a large portion of natural grasslands has been converted to agricultural cropland or other land uses, while the remaining natural grasslands are mainly used as rangeland. However, with increasing crop demand and food security concerns, there is a potential risk of further grassland conversion to cropland, particularly in areas where climate change may enhance suitability for farming. Here, we (1) quantified the impact of the present state of grasslands on maintaining landscape permeability; and (2) determined how the conversion of remaining grasslands to croplands could affect structural landscape connectivity at multiple spatial scales. We simulated four progressive scenarios of grassland conversion to cropland, starting with grasslands identified as most suitable for farming. Our results revealed that structural landscape connectivity, quantified as mean normalized current density with resistance values based on naturalness, decreased by up to 43% in southwestern and central areas of the Parkland and Grassland regions with higher rates of conversion. Conversion scenarios introduced new areas with notably constrained ecological flow in the Grassland region in the southeastern part of the province. Conversely, increased current density was observed in the Rocky Mountain and Boreal regions, which appear to act as alternative pathways for redirected ecological flow. Future grassland conversion is expected to further shift current flow from the grasslands westward through the foothills of the Rocky Mountain and northward into the Parkland and Boreal regions. These findings underscore the critical role of grasslands in maintaining structural landscape connectivity across Alberta, which is essential for supporting biodiversity and gene flow among species. Simulated changes in connectivity were most pronounced at the finer spatial scale, revealing key areas of past and future permeability shifts. Incorporating local land management decisions is crucial for improving landscape permeability and effective connectivity planning province-wide.